1996
DOI: 10.1128/aem.62.11.4238-4242.1996
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microbial growth by ajoene, a sulfur-containing compound derived from garlic

Abstract: Ajoene, a garlic-derived sulfur-containing compound that prevents platelet aggregation, exhibited broadspectrum antimicrobial activity. Growth of gram-positive bacteria, such as Bacillus cereus, Bacillus subtilis, Mycobacterium smegmatis, and Streptomyces griseus, was inhibited at 5 g of ajoene per ml. Staphylococcus aureus and Lactobacillus plantarum also were inhibited below 20 g of ajoene per ml. For gram-negative bacteria, such as Escherichia coli, Klebsiella pneumoniae, and Xanthomonas maltophilia, MICs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(67 citation statements)
references
References 16 publications
5
59
0
3
Order By: Relevance
“…Furthermore, many studies suggested that DATTS provided a potent antimicrobial activity (Rattanachaikunsopon & Phumkhachorn, 2008). The antimicrobial potential of GEO has been demonstrated to increase with the number of disulphide groups, corresponding to relative MIC values of DATTS < DATS < DADS, in controlling B. cereus, L. monocytogenes, S. aureus and E. coli (Naganawa et al, 1996;Rattanachaikunsopon & Phumkhachorn, 2008). Therefore, chitosan-pectin hydrogel beads loaded with GEO+H-BEO at 1:1, v/v could expectedly inhibit a wide range of microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, many studies suggested that DATTS provided a potent antimicrobial activity (Rattanachaikunsopon & Phumkhachorn, 2008). The antimicrobial potential of GEO has been demonstrated to increase with the number of disulphide groups, corresponding to relative MIC values of DATTS < DATS < DADS, in controlling B. cereus, L. monocytogenes, S. aureus and E. coli (Naganawa et al, 1996;Rattanachaikunsopon & Phumkhachorn, 2008). Therefore, chitosan-pectin hydrogel beads loaded with GEO+H-BEO at 1:1, v/v could expectedly inhibit a wide range of microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…GEO (sample A, B) was comprised of DADS (31.67%, 27.19%), DATS (31.56%, 42.49%) and DATTS (13.48%, 9.92%), respectively. Several works reported that garlic oil has strong antimicrobial potency due to its disulphide groups (Naganawa et al, 1996;Hyldgaard et al, 2012;Pirak et al, 2012;El-sayed et al, 2017). Antimicrobial activity of GEO increased with the number of disulphide groups, corresponding to relative MIC values of DATTS < DATS < DADS (Kim et al, 2004;Kyung, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…GEO sample B showed a similar antimicrobial pattern, except a moderate inhibition against S. typhimurium (10.50 mm). Previous studies found Gram-positive bacteria, such as B. cereus and S. aureus, to be susceptible to EOs, while Gram-negative bacteria, such as E. coli and S. enterica, were more resistant (Naganawa et al, 1996;Boufadi et al, 2016;El-sayed et al, 2017;Trinetta et al, 2017). Gram-negative bacteria have an outer layer of hydrophilic lipopolysaccharide, which acts as a barrier between the cytoplasmic membrane and hydrophilic compounds, protecting the cell membrane from volatile diffusion (Burt, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Middle Ages, it was used to treat plague and cholera and in the World War I for curing wounds. Anti-bacterial activity of garlic is known from Pasteur since 1858 and its anti-proliferative, proapoptotic, anti-tumoral, anti-viral and anti-platelet aggregation properties are known for 50 years [1][2][3][4][5][6][7][8][9][10][11]. Garlic's efficacy depends on the activity of products resulting from the breakage of alliin into allicin.…”
Section: Introductionmentioning
confidence: 99%